Psychomotor Seizure Test, Neurotoxicity and in vitro Neuroprotection Assay of some Semicarbazone Analogues - Jawed Ahsan, Mohamed; P. Stables, James (Central Nervous System Agents in Medicinal Chemistry, 2013)
In continuance of our search for anticonvulsant agents, we reported herein the synthesis, characterization and anticonvulsant evaluation of some newer semicarbazone analogues. A few compounds were also screened for neuroprotection assay. Some of the compounds showed significant anticonvulsant activity. Compound 4a showed 25% (1/4, 0.25 h), 75% (3/4, 0.5 & 2.0 h) and 100% (4/4, 1.0 h) protection against 6 Hz psychomotor seizure test at 100 mg/kg devoid of any neurotoxicity. Compound 4d showed neuroprotection activity with 26.3 ± 2.3 percent of total propidium iodide uptake at 100 µM and IC50 of the compound was calculated using dose response curve by probit analysis and was found to be 149 ± 1.22 µM.
Keywords: 6 Hz psychomotor seizure test